A study of the effects of interpersonal interaction on the users' preference to libraries and library services in UP Diliman - Simon, George Marcell P.; Obille, Kathleen Lourdes B. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2011)
Different feedback mechanisms have been explored in evaluating libraries and the services they render. Some focus on the collections, others on facilities, and then some evaluate how the librarians conduct themselves to users and patrons of the library. The notion of observing the interaction between the librarian and the users is a relatively new concept, much more the idea of observing interpersonal interactions between the users themselves. The study determined if the interpersonal interactions in the library affect a user's preference in choosing a library to seek information and other library-related services. The study sampled 232 undergraduate students, who were then asked to rank their preferred libraries in UP Diliman and respond to various situations stated in the survey.
Based on the survey, it was determined that interaction between users was limited, and that most users prefer to not approach other people in the library unless it is for information-seeking purposes. Most interaction occurred with the library staff and users, particularly when looking for a primary source of reference. Also, interpersonal interactions can positively and negatively affect preference to a specific library, e.g., if negatively affected, a user can be driven to look for information elsewhere or avoid said library altogether. It was also observed that, given an alternative source of information, preference can supersede information need, to avoid further unwanted interactions in the library that received unfavorable reactions
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: University of the Philippines (Diliman) -- Students; Social perception